Analisis Kinerja Reksa Dana yang Terdaftar di Bapepam Menurut Metode Risk Adjusted Return - Nadia Asandimitra; Nurul Rizqia V. Lumaela (BISMA (Bisnis dan Manajemen), 2018)
Mutual Fund is one investment instruments, especially for small scale investor who doesnt have many time and expertise to calculate the risk over their investment. Because through mutual fund, an investor could reliance his fund to be managed by investor management in which to be diversified broadly in order to give business advantage for the investor. Mutual fund fixed revenue is accumulative society fund which is invested in to encumber, generally in form of obligation. Mutual fund share is accumulative fund which is invested in to the combination between encumber and share with allocation that cannot be categorized in to mutual fund money market, mutual fund fix revenue, and mutual fund share. Performance analysis method for mutual fund can use risk adjusted return method, because performance measurement not only evaluated from the amount of mutual fund but also the risk that involved on it. Result of performance analysis of mutual fund in Indonesia, in year evaluated between 2004 2007 can be described as follows in general, mutual fund performance according to  Sharpe, Treynor, Jensen methods shows that in under perform position, only in 2004, 2005,2006 according to Jensen and Treynor methods shows that Schorder Prestasi Plus, Capital TRIM and  Fortis Pesona who has out perform position. Mutual fund performance that in under performance offer 2004 2007 was caused by highly return risk free condition in Indonesia. Lack of knowledge of Indonesian investor about mutual fund was the main problem.